Srategi Bauran Pemasaran Pelayanan Kesehatan RSD Kol. Abundjani Bangko di Era Jaminan Kesehatan Nasional (JKN) - Arismen, Arismen; Sulistiadi, Wahyu; Sjaaf, Amal Chalik (UI Scholars Hub, 2019)
The policy developed by the government in the form of a National Health Insurance (JKN) program whose funding is managed by the BPJS, must be supported by all health service facilities both government and private. RSD Kol. Abundjani Bangko is a regional hospital belonging to the Merangin District Government that has collaborated with BPJS to serve BPJS participants in the health services sector in 2014. In the course of the increase there have been an increase in the number of BPJS participants who have been referred and treated to RSD Kol. Abundjani Bangko. The increase in patient visits on the one hand was pleasing to management and on the other hand raised concerns for the management of RSD Kol. Abundjani Bangko. This concern arose since the budget deficit managed by the BPJS, resulting in delays in disbursing claims for patient services to BPJS participants and this affected the operations of hospitals in giving and maintaining the quality of health services. To ensure the operation of health services in hospitals, management must have a marketing strategy in the BPJS era so that hospitals can continue to provide services and not cause complaints from customers or patients. This study tries to describe the marketing strategy with the marketing mix pattern that includes 7P (product, price, promotion, place, people, process, and physical facility). The purpose of this study was to see an overview of the application of the marketing strategy by means of the marketing mix (marketing mix) of the health services of RSD Kol.Abundjani Bangko era BPJS. The research results obtained are with the marketing mix strategy. RSD Kol. Abundjani Bangko can still provide quality services to patients with conditions in the era BPJS that have a budget deficit